To find each sum in the table, we will add the values in columns \( a \) and \( b \).
Let’s calculate each sum:
-
For \( a = 1 \) and \( b = 2 \): \[ 1 + 2 = 3 \] So, \( a + b = 3 \).
-
For \( a = -1 \) and \( b = -2 \): \[ -1 + (-2) = -1 - 2 = -3 \] So, \( R = -3 \).
-
For \( a = -4 \) and \( b = 1 \): \[ -4 + 1 = -3 \] So, \( S = -3 \).
-
For \( a = -6 \) and \( b = -3 \): \[ -6 + (-3) = -6 - 3 = -9 \] So, \( T = -9 \).
Now we can complete the table:
- First row: \( 3 \)
- Second row: \( R = -3 \)
- Third row: \( S = -3 \)
- Fourth row: \( T = -9 \)
Final results:
\[ R = -3 \] \[ S = -3 \] \[ T = -9 \]